Chapter 3 Is It Possible to Prevent Unforeseen Events? - Rundmo, Torbjørn (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"An unforeseen event may be defined as something that happens suddenly and unexpectedly. Such events are seldom the result of an organisation's operational planning, but they can be side-effects of such planning. An unforeseen event may have either positive or negative consequences. This chapter aims to discuss if it is possible to prevent unforeseen events. The major focus is on analysis and prevention of unforeseen events with negative consequences, such as accidents, catastrophes and acts of terror. Such events often take place in complex systems, and failures of appropriate organisational interaction and communication among participants with complementary competence in such systems may contribute to unforeseen events. Risk-analysis methods and tools based on energy-barrier models, causal sequence and process models, as well as information-processing models are presented and their applicability to the prevention of unforeseen events is discussed. This also includes the Bow-tie approach, as well as other approaches which take into consideration organisational factors and social interaction (samhandling). The conclusion is that unforeseen events can be prevented. However, in the aftermath of the implementation of safety and security measures, it is not possible to know which events they prevented, or to obtain knowledge about their efficiency. An additional strategy for prevention of unforeseen events with negative consequences is proposed."